MOTIVES AND THEIR DIFFERENCES IN FRENCH AND UZBEK FAIRY TALES - Narzulloyev Bekzod (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
Fairy tale" has a wide potential as a form of morals and education in the development of the young generation. It develops the student's thinking, prepares the mind, organizes it. "Ertak" educates young people in the spirit of teaching and advice, and forms the qualities of goal orientation, logical thinking, resourcefulness in students. The fairy tale is the most ancient and popular example of artistic prose in folklore. A child grows up listening to fairy tales from a very young age. Adults tell fairy tales to entertain children, and children themselves start telling small fairy tales when they grow up and start going to school. The stories that these children tell each other are partly what they heard from adults, and partly what they tell themselves. Yu. The Sokolovs must have meant this: "The stories told by children to each other were almost not recorded," they regretted.